Use of claims data to estimate annual cervical cancer screening percentages in Portland metropolitan area, Oregon. (April 2016) - Abdullah, Nasreen; Laing, Robert S.; Hariri, Susan; Young, Collette M.; Schafer, Sean
Highlights: Human papillomavirus (HPV) vaccine should reduce cervical dysplasia before cervical cancer. Diagnosis of dysplasia is screening-dependent. Study introduces novel method to calculate estimates of Pap screening. Abstract: Background: Human papillomavirus (HPV) vaccine should reduce cervical dysplasia before cervical cancer. However, dysplasia diagnosis is screening-dependent. Accurate screening estimates are needed. Purpose: To estimate the percentage of women in a geographic population that has had cervical cancer screening. Methods: We analyzed claims data for (Papanicolau) Pap tests from 2008–2012 to estimate the percentage of insured women aged 18–39 years screened. We estimated screening in uninsured women by dividing the percentage of insured Behavioral Risk Factor Surveillance Survey respondents reporting previous-year testing by the percentage of uninsured respondents reporting previous-year testing, and multiplying this ratio by claims-based estimates of insured women with previous-year screening. We calculated a simple weighted average of the two estimates to estimate overall screening percentage. We estimated credible intervals using Monte-Carlo simulations. Results: During 2008–2012, an annual average of 29.6% of women aged 18–39 years were screened. Screening increased from 2008 to 2009 in all age groups. During 2009–2012, the screening percentages decreased for all groups, but declined most in women aged 18–20 years, from 21.5% to 5.4%. Within age groups, compared to 2009, credible intervals did not overlap during 2011 (except age group 21–29 years) and 2012, and credible intervals in the 18–20 year group did not overlap with older groups in any year. Conclusions: This introduces a novel method to estimate population-level cervical cancer screening. Overall, percentage of women screened in Portland, Oregon fell following changes in screening recommendations released in 2009 and later modified in 2012.